ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA DE TRANSPORTE ESCOLAR EN LA CIUDAD DE ALAMOR, CANTON PUYANGO, PROVINCIA DE LOJA - Chasi Carrión, Juan Pablo (2016)
The project aims to implement a business run School Transportation in the city of Alamor thus meeting the needs of families of Alamor transporting their children safely to their schools different way. To start with the study of this project, it has set a general target named: Develop a feasibility study for the creation of a business school transport in the city of Alamor, Puyango Canton province of Loja, which raised specific objectives who served as guide for the study. To meet this primary objective methods, techniques and procedures that allowed research, develop and test the veracity of the project were used. The methods used were; Deductive, which it allowed based on the theoretical concepts related to the realization of an investment project application in the development of market research, technical, organizational, economic and financial; Inductive: This method based on the characteristics found in the project feasibility, generalized conclusions and recommendations are used. Direct Observation: The following techniques are applied allowed to know whether there is in the city of Alamor companies dedicated to school transport service, the Survey: Applied to a representative sample of the population of families in the city of Alamor to determine the need and preferences of the target market in relation to school transport service, vital for the establishment of the demand, supply and unsatisfied demand service to offer information. Total of 350 surveys, the total study population 3,964 families. For the study and analysis of the Offer, it interviewed 2 vehicle owners one taxi company and other informal vehicle. 5 The analysis in the development of each of the phases of the project feasibility allowed to reach the following: Market Research; It determines that the company is feasible to implement it according to the data obtained an unmet demand for 3,383 families for the first year was obtained. Within the financial paper; the amount of the investment will be funded entirely by the three partners giving a value of each $ 18.494.72; the breakeven analysis allowed to know that for the first year the company will use an installed capacity of 67.55% and should have sales of $ 36.480.54, so the company does not win or lose The financial evaluation indicates that the NPV is 7.244.01, an IRR of 26.69%, the company regained capital in 2 years 5 months 4 days; that for every dollar invested in the company earns 0.43 ctv., and that the company is very sensitive to increased costs and diminution of income, determining that implementing this type of venture is feasible in the city of Alamor Based on the results, it is recommended to implement the project as it will give significant returns for its investors and contributing to the improvement of society.